(untitled) (International Conference on Modern Science and Scientific Studies, 2025)
Rheumatoid arthritis is an immune-inflammatory rheumatic disease characterized by progressive destruction of joints and damage to internal organs, the development of which is determined by a complex interaction of environmental factors and genetic predisposition, leading to global disturbances in the humoral and cellular immunity system [1, 2]. The heterogeneity of the pathogenetic mechanisms of rheumatoid arthritis is reflected in the existence of a wide range of phenotypes and endotypes of the disease, which allows us to consider it not as “one disease,” but as a clinical and immunological syndrome [3, 4].